Developing and Validating the Teacher Self-Efficacy for Teaching Students with Autism Spectrum Disorder (TSE-ASD) Scale - Nazari, Nabi (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Background: Autism spectrum disorder (ASD) continues to rise at an astonishing rate. As many schools attempt to create an inclusive environment conducive for students with autism to support academic success, we must recognize the teacher’s role in creating an inclusive classroom. Using a student-specific teaching self-efficacy measure might provide more useful information for supporting teachers’ beliefs for teaching students with ASD. Teachers with high self-efficacy have a positive impact on student achievement. The purpose of this investigation was to develop an instrument that can be used to measure teachers’ self-efficacy for effectively working with students with ASD. The original version of the scale was translated and back-translated into Persian, followed by a pilot study. A sample (n=633) of university students was recruited. Results indicated that the scale represented a unidimensional construct with acceptable internal consistency. Exploratory factor analysis demonstrated the unidimensionality of the TSE-ASD. The maximum likelihood confirmatory for the 12-item TSE-ASD model indicated excellent model fit indices (χ2/df=2.60, CFI=0.956, SRMR=0.049, PCLOSE >0.05, RMSEA=0.062, 90% CI [0.052, 0.082]). As for criterion-related validity, The Pearson correlation coefficients between (TSE-ASD score) and self-regulation (r= 0.72, p<0.01) revealed a large correlation and linear regression indicating that TSE-ASD significantly predicted self-regulation, b = 0.69, p < 0.001. Using a student-specific teaching self-efficacy measure might provide more useful information for supporting teachers’ beliefs for teaching students with ASD. The findings provide evidence that TSE-ASD is a reliable and valid instrument for assessing teacher self-efficacy for teaching students with Autism Spectrum Disorder in educational settings among Persian speaking individuals.